THE EFFECTIVENESS OF USING ARTIFICIAL INTELLIGENCE APPLICATIONS IN SOLVING HOMEWORK ASSIGNMENTS ON STUDENT ACHIEVEMENT IN CHEMISTRY FROM THE PERSPECTIVE OF TEACHERS IN IRAQ - Al-Bayati, Kareem Ahmed Mohammed (Academic Journal Research, 2025)
Objective: This study aimed to examine the effectiveness of artificial intelligence (AI) applications used in homework completion on students’ chemistry achievement as perceived by teachers in Iraq. Method: A descriptive analytical design was employed, targeting all chemistry teachers in preparatory and secondary schools under the Directorate of Education in Kirkuk Governorate for the academic year 2024/2025. A randomly selected sample of 120 teachers participated by completing a validated and reliable questionnaire consisting of demographic information and three core domains measured on a five-point Likert scale. Results: The findings indicated that students’ use of AI applications positively influenced their chemistry achievement (overall mean = 3.91; agreement rate = 78.2%). Sub-results further showed that AI usage ranged from moderate to high, with teachers acknowledging its benefits while expressing concerns regarding overdependence on ready-made solutions and difficulty distinguishing students’ original work from AI-generated outputs. Novelty: This study contributes new insights into teacher perceptions of AI-assisted homework within the Iraqi educational context, highlighting ethical use, regulatory needs, and teacher training as strategic priorities, and offering directions for future research integrating AI with active learning approaches.